Effect of plant growth regulators on growth and yield of chili (Capsicum annuum L.) - Anolisa, .; Hossen, Md. Al-Imran, Riyad; Islam, A.T.M. Rafiqul; Das, Subroto Kumar (Journal of Phytology, 2020)
Chili (Capsicum annuum L.) is an important food additive with high medicinal value. To investigate the effect of plant growth regulators on chili, seedlings of chili were collected from the local market and grown in the experimental field of the University of Barishal, Bangladesh. Foliar spray of different degrees of plant growth regulators, Gibberellin (50 mg/l, 100 mg/l, 250mg/l, 350 mg/l GA3) and Cytokinin (50 mg/l, 100 mg/l, 250mg/l, 350mg/l Kn) were applied from 15 days of germination. Data on different growth and yield parameters were collected and analyzed statistically. The result reveals that there is a significant difference in growth and yield related traits in chili due to the application of plant growth regulators. An optimum level of PGRs application shows better performance compare with control. Plant height particularly influenced by GA3 whereas other attributes like the number of leaves, branches, flowers and fruits are greatly influenced by the application of kinetin.